Regulatory mechanisms of tetramethylpyrazine on central nervous system diseases: A review - Liu, Yue; Yang, Guang; Cui, Wenqiang; Zhang, Yunling; Liang, Xiao (Frontiers in Pharmacology, 2022)
Central nervous system (CNS) diseases can lead to motor, sensory, speech and cognitive dysfunction and even death, causing a huge socio-economic burden. Tetramethylpyrazine (TMP) is one of the main active ingredients extracted from Chinese herbal medicine Ligusticum striatum DC. (Chuan Xiong). Many in vivo and in vitro studies have demonstrated that TMP has a certain role in the treatment of CNS diseases through inhibiting calcium ion overload and glutamate excitotoxicity, anti-oxidatve/nitrification stress, mitigating inflammatory response, anti-apoptosis, protecting the integrity of BBB and facilitating synaptic plasticity. In this review, we summarize the roles and mechanisms of TMP on ischemic cerebrovascular disease, spinal cord injury, Parkinson’s disease, Alzheimer’s disease, cognitive impairments, migraine and depression. We hope to facilitate the clinical application of TMP and provide a basis and direction for the development of new drugs.